2021
DOI: 10.1039/d1nr05379e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient single-photon pair generation by spontaneous parametric down-conversion in nonlinear plasmonic metasurfaces

Abstract: The presented work demonstrates a new efficient ultrathin entangled single-photon pair nanophotonic source based on spontaneous parametric down-conversion working at room temperature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…42 Here, resonant enhancement of the photonic density of states led to higher generation rates when degenerate signal and idler wavelengths were close to the grating resonance, as shown in Figure 5d. Furthermore, silver nanogratings on thinfilm LiNbO 3 sustaining plasmon-polariton resonances at different wavelengths were numerically shown to mediate nondegenerate SPDC, 163 but the metal-induced losses decreased the achievable conversion efficiency (see row 6 in Table 3). Metasurfaces from nanostructured thin-film LiNbO 3 were also used for photon-pair generation (see Figure 5e).…”
Section: Engineering Spontaneous Parametric Down-conversionmentioning
confidence: 99%
“…42 Here, resonant enhancement of the photonic density of states led to higher generation rates when degenerate signal and idler wavelengths were close to the grating resonance, as shown in Figure 5d. Furthermore, silver nanogratings on thinfilm LiNbO 3 sustaining plasmon-polariton resonances at different wavelengths were numerically shown to mediate nondegenerate SPDC, 163 but the metal-induced losses decreased the achievable conversion efficiency (see row 6 in Table 3). Metasurfaces from nanostructured thin-film LiNbO 3 were also used for photon-pair generation (see Figure 5e).…”
Section: Engineering Spontaneous Parametric Down-conversionmentioning
confidence: 99%
“…With high second-order susceptibility, LN also plays an essential role in improving the efficiency of the nonlinear effect. Jin et al 160 used the LN and plasmonic configuration to generate highly directional entangled photon pairs. They simulated a Metal−Insulator−Metal structure, as shown in Figure 11d.…”
Section: ■ Nonclassical Metasurfacementioning
confidence: 99%
“…(d) Plasmonic boosted entangled photon pair generation . Reprinted with permission from ref . Copyright 2021 Royal Society of Chemistry.…”
Section: Nonclassical Metasurfacementioning
confidence: 99%
“…An enhancement of SPDC through localized Mie-type optical resonances (16) in nanoantennas (17) and metasurfaces (18) was experimentally demonstrated. Recent theoretical studies (19)(20)(21) suggested that using metasurfaces with nonlocal lattice resonances (22,23) can further boost the SPDC efficiency, yet the realization of this concept remained outstanding.…”
Section: Introductionmentioning
confidence: 99%